Pembuatan dan Implementasi Visual Effect untuk Video Podcast dengan Menggunakan VMix - Murdaningtyas, Citra Devi; Astin, Novita; Fachri, M Julias (Universitas Negeri Padang, 2024)
Visual effects commonly referred to as VFX, is a computerized process in which images or object models are created and manipulated, involving integrating digital effects recordings and special effects from a computer to create a virtual environment. In this modern era, the digital industry is growing more rapidly because the increasingly diverse visual effects technology mainly influences it. Applying VFX to audio-video formatted podcasts can solve the podcast visual display problem. The visuals presented in the video podcast content are mostly monotonous (repeated displays), so they look dull. Besides that, the appearance of the video shown is less informative because it only observes the podcaster and the speaker who is talking without any visual aids. This study discusses the creation and implementation of VFX on podcasts. The VFX produced in this study includes one virtual set background and six visual effect templates. Based on the results of expert reviews, VFX is suitable to be implemented in podcasts and can add to the aesthetic value of a video podcast. In addition, although VFX cannot produce additional information value, VFX can make the delivery of information more comfortable for the audience.